Eletrofiação de nanofibras de fibroína da seda como dispositivos adsorventes para microextração em fase sólida - Muller, Vinicius (2014)
Electrospinning technique was applied in the covering of fused silica fibers by regenerated silk fibroin nanofibers (RSF). The parameters of electrospinning process were evaluated through factorial experimental design 22. This study showed the variables flow of solution and capillary-collector distance were statistically significant in the medium diameter response. The model obtained was validated through variance analysis (ANOVA) and response surface methodology. The material was used at solid phase micro extraction (SPME) in the extraction of samples containing a small chain alcohol, applied at gas chromatography (GC). The recovered device was characterized through Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR) and thermal analysis (DSC and TGA). The RSF nanofibers covered fibers were morphologic evaluated through scanning electronic spectroscopy (MEV). The results of MEV showed that was possible to obtain fibers in nanoscale, medium diameter around 304 ± 46 nm. The fibers were also submitted to simulated thermal treatment (100°C to 250°C). There was no fusion between the fibers until 250°C (4 hours of treatment), and a little structural damage. The thermal analysis of FRS and covered FRS nanofibers device showed that the electrospun material maintained the thermal stability, with loss due thermal degradation from 250°C. The GC assay demonstrated the standard SPME covered device didn´t interfere on the suggested method to the alcohol isopropyl analysis (AIS). The times of extraction and desorption were optimized in 20 minutes and 10 minutes, respectively. The methodology was evaluated about linearity and specificity. In the concentration between 10 to 500 ppm of AIS, the method was linear, with R2= 0,9927 and selective, with high resolution between peaks of methanol, AIS and ethyl acetate. Electrospinning process of RSF as covering device showed great potential to use in SPME due its high surface area, thermal stability and easiness process, as well as potential to application in extraction of alcohols and GC analysis.